MULTI-CHANNEL DEVICE FOR CONTROL OF DEFECTS OF FABRIC SURFACE (Academia Science Repository, 2023)
The current problem of controlling the technological parameters of the fabric during their primary processing is highlighted. The structural diagrams and the principle of operation of visual-optical and radiation methods and devices for controlling the intraspot of the tissue shell are presented. It has been established that optoelectronic methods and devices for monitoring technological parameters of co-cones are more promising.